The inflammatory and metabolic status of patients with sudden-onset sensorineural hearing loss - do Amaral, Jônatas Bussador; Peron, Kelly Abdo; Soeiro, Tracy Lima Tavares; Scott, Marina Cançado Passarelli; Hortense, Flávia Tatiana Pedrolo; da Silva, Michelly Damasceno; França, Carolina Nunes; Nali, Luiz Henrique da Silva; Bachi, André Luis Lacerda; de Oliveira Penido, Norma (Frontiers in Neurology, 2024)
Introduction Sudden sensorineural hearing loss (SSNHL) is a common emergency symptom in otolaryngology that requires immediate diagnosis and treatment. SSNHL has a multifactorial etiology, and its pathophysiologic mechanisms may be associated with inflammatory and metabolic changes that may affect the cochlear microenvironment or its nervous component, thus triggering the process or hindering hearing recovery. Therefore, the aim of this study was to assess metabolic and inflammatory changes to identify systemic parameters that could serve as prognostic factors for hearing recovery in patients with SSNHL. Materials and methods Thirty patients with a sudden hearing loss of at least 30 dB in three contiguous frequencies were enrolled in this study. Patients were followed up for 4 months and peripheral blood samples were collected at 7 days (V1), 30 days (V2) and 120 days (V3). Interleukins (IL)-1F7, IL-2, IL-4, IL-5, IL-6, IL-10, interferon γ (IFN-γ), tumor necrosis factor α (TNF-α) and adiponectin were quantified in serum. In addition, lipid and glycemic profiles as well as concentration of creatinine, uric acid, fructosamine, peroxide, total proteins and albumin were analyzed. Patients underwent weekly ear-specific hearing tests with standard pure tone thresholds for frequencies of 250–8,000 Hz, speech recognition threshold and word recognition score. Results Patients with SSNHL were divided into a group of patients who did not achieve hearing recovery (n = 14) and another group who achieved complete and significant recovery (n = 16). Most serologic parameters showed no significant changes or values indicating clinical changes. However, IFN-γ levels decreased by 36.3% between V1 and V2. The cytokine TNF-α showed a statistically significant decrease from V1 to V3 (from 22.91 to 10.34 pg./mL). Adiponectin showed a decrease from 553.7 ng/mL in V1 to 454.4 ng/mL in V3. Discussion Our results show that serologic cytokine levels change in the acute phase of manifestation of SSNHL and establish a parallel between systemic changes and improvements in hearing, especially TNF-α, which showed differences in hearing recovery. The use of IFN-γ, TNF-α and adiponectin may elucidate the clinical improvement in these patients.